On Monotone Asymptotic Pointwise Nonexpansive Mappings in Modular Function Spaces - B. A. Bin Dehaish (Journal of Function Spaces)
In this work, we investigate the existence of the fixed points of a monotone asymptotic pointwise nonexpansive mapping defined in a modular function space. Our result extends the fixed point result of Khamsi and Kozlowski.